Network Pharmacology-Based Strategy for Elucidating the Molecular Basis Forthe Pharmacologic Effects of Licorice (Glycyrrhiza spp.) - Chen, Jia; Li, Lin-Fu; Hu, Xiao-Ru; Wei, Feng; Ma, Shuangcheng (Frontiers in Pharmacology, 2021)
Licorice (Glycyrrhiza spp.) is widely used in traditional Chinese medicine (TCM) for its numerous pharmacologic effects. However, the mechanisms of action of the chemical constituents of licorice and their structure–function relationships are not fully understood. To address these points, we analyzed the chemical compounds in licorice listed in the TCM Systems Pharmacology Database and TCM Integrated Database. Target proteins of the compounds were predicted using Integrative Pharmacology-based Research Platform of TCM v2.0. Information on the pharmacologic effects of licorice was obtained from the 2015 Chinese Pharmacopoeia, and disease-related genes that have been linked to these effects were identified from the Encyclopedia of TCM database. Kyoto Encyclopedia of Genes and Genomes pathway analysis was carried out for the target proteins, and pharmacologic networks were constructed based on drug target–disease gene and protein–protein interactions. A total of 451 compounds were analyzed, of which 211 were from the medicinal parts of the licorice plant. The 241 putative targets of 106 bioactive compounds in licorice included 52 flavonoids, 47 triterpenoids, and 7 coumarins. Four distinct pharmacologic effects of licorice were defined: 61 major hubs were the putative targets of 23 compounds in the heat-clearing and detoxifying effects; 68 were targets of 6 compounds in the spleen-invigorating and qi-replenishing effects; 28 were targets of 6 compounds in the phlegm expulsion and cough-suppressant effects; and 25 were targets of 6 compounds in the spasm-relieving and analgesic effects. The major bioactive compounds of licorice had been identified by UHPLC-QTOF-MS/MS. The anti-inflammatory properties of liquiritin apioside, liquiritigenin, glycyrrhizic acid and isoliquiritin apioside were demonstrated by enzyme‑linked immunosorbent assay (ELISA) and Western blot analysis. Liquiritin apioside, liquiritigenin, isoliquiritigenin, isoliquiritin apioside, kaempferol, and kumatakenin were the main active flavonoids; and 18α- and 18β-glycyrrhetinic acid were the main active triterpenoids. The former were associated with heat-clearing and detoxifying effects, whereas the latter were implicated in the other 3 pharmacologic effects. Thus, the compounds in licorice have distinct pharmacologic effects according to their chemical structure. These results provide a reference for investigating the therapeutic potential of licorice in the treatment of various diseases.